(untitled) (Fiep Bulletin - online, 2011)
The survey was to assess the levels of pain in women with cancer of the city of Belém-PA. It was realized at interview form. The sample was composed by 35 patients enrolled and serviced by AVAO- Voluntary Association to Support the Oncology, of the town of Belém-PA, females, with average age of 56,28 (± 8.68) years, diagnosed with the following types: breast, 46%; cervix, 37%; and other types of cancer, 17%. To conduct the research, it was used the question number 9 of the European Organization Research and Treatment of Cancer Questionnaire of Quality of Life (EORTC QLQ-c-30), which consists in the following question: "during the last week, did you have pain?". This issue has four possible answers, a Likert scale type,of 4 scores(i.e.: no- score 1 ; less- score 2; moderately- score 3; and much- score 4).83% of patients reported that have pain, because of the treatment and the disease itself, in the week before the interview, with answers distributed this way: 31% marked the option "so much– score 4"; 29% marked the option ’ moderately – score 3"; and 23% scored " a little – score 2". Only 17% marked the answer "No – score 1", affirming that they have no pain in the week preceding the interview.